Fish and hydropower on the U.S. Atlantic coast: failed fisheries policies from half‐way technologies. Issue 4 (16th January 2013) - Brown, J. Jed; Limburg, Karin E.; Waldman, John R.; Stephenson, Kurt; Glenn, Edward P.; Juanes, Francis; Jordaan, Adrian
Abstract Globally, diadromous species are at risk from fragmentation by damming of rivers, and a host of other anthropogenic factors. On the United States Atlantic Coast, where diadromous fish populations have undergone dramatic declines, restoration programs based on fishway construction and hatcheries have sustained remnant populations, but large‐scale restoration has not been achieved. We examine anadromous fish restoration programs on three large Atlantic Coast rivers, the Susquehanna, Connecticut, and Merrimack with multiple mainstem hydropower dams, most with relatively low generating capacity. Mean passage efficiencies through fishways on these rivers from the first dam to the spawning grounds for American shad are less than 3%. The result is that only small fractions of targeted fish species are able to complete migrations. It may be time to admit failure of fish passage and hatchery‐based restoration programs and acknowledge that significant diadromous species restoration is not possible without dam removals. The approach being employed on the Penobscot River, where dams are being removed or provided the opportunity to increase power generation within a plan to provide increased access to habitat, offers a good model for restoration. Dammed Atlantic Coastal rivers offer a cautionary tale for developing nations intent on hydropower development, suggesting that lasting ecosystem‐wide impacts cannot be compensated for through fish passage and hatchery technology.